ANALISIS HATCH COVER DERAILED PADA PROSES CARGO HOLD CLEAN-ING GUNA MENUNJANG KELANCARAN PEMUATAN PADA MV. KENCANA BARUNA - akbar, syafiq; Baskoro, Bayu Yudho; Rochmansyah, Rizal; Kurniawan, Muhammad; Hidayah, Ferro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Hatch covers are one of the vital components on bulk carriers that serve to protect cargo and support the smooth loading and unloading process. In practice, disturbances in the form of derailed hatch covers still often occur, especially during cargo hold cleaning, which can hinder the loading process and potentially pose occupational safety risks. This study aims to analyze the causes of hatch cover derailment during the cargo hold cleaning process and formulate technical and operational measures to support the smooth loading process on MV Kencana Baruna. The research method used is a qualitative descriptive method with data collection techniques through direct observation on the ship, interviews with relevant crew members, and documentation studies of hatch cover procedures and maintenance records. The results of the analysis show that the main factors causing hatch cover derailment include lack of maintenance of the hatch cover track, suboptimal roller conditions, and lack of supervision and implementation of appropriate work procedures during the cargo hold cleaning process. Preventive measures that can be taken include improving the periodic maintenance program, checking the condition of the hatch cover before and after cleaning, and improving crew discipline in implementing standard operating procedures.